Application of Interactive Virtual Lab Media Based on a STEM Approach in Improving Students' Scientific Literacy and Learning Motivation - Eva Pratiwi Pane; Nenni Faridah Lubis; Gayus Simarmata (Jurnal Penelitian Pendidikan IPA, 2024)
One of the developments in the world of education is using virtual labs as a medium for carrying out practical work. The aim of this research is to determine the application of using interactive virtual lab practicum media based on a STEM approach in increasing students' scientific literacy and learning motivation. The subjects of this research were students in the odd semester of the 2023/2024 academic year who took basic chemistry practical lectures on the topic of reaction rates. The research method uses a quantitative approach with a quasi-experimental design in the form of a one group pretest and posttest design. The instruments used in this research were a multiple-choice test to measure scientific literacy and a questionnaire to measure learning motivation. Data analysis in this study used descriptive statistics including n-gain and percentage calculations. Based on the results of data analysis, it was found that the increase in students' scientific literacy was 0.46 with moderate criteria. Scientific literacy skills have increased significantly in the aspect of explaining scientific phenomena by 82%. Student learning motivation also increased with an average of 77% before learning to 83% after learning.